Technology lifecycle-oriented search for production technologies. (January 2017) - Greitemann, Josef; Zaggl, Michael A.; Hehl, Martin; Raasch, Christina; Reinhart, Gunther
Abstract: The adoption of production technologies is a major challenge for manufacturing companies. Despite the long term impact of decisions on production technologies, companies are often unaware how to search for alternative production technologies. We developed a method that focusses on the systematic search for production technologies for fulfilling future manufacturing tasks. The method consists of three steps including the selection of information sources, information search and information evaluation. It takes advantages of the concept of technology lifecycles. The method provides a useful tool for producing companies and has been applied exemplary in the automotive industry.